ANALISIS TINDAK PIDANA NARKOTIKA BERDASARKAN PUTUSAN PENGADILAN NEGERI MAKASSAR REGISTER PERKARA NO.816/PID.SUS/2023/PN. Mks. - Iskandar, Umar; Faisal Alwi (Journal of Innovation Research and Knowledge, 2024)
In the context of legal proceedings, courts evaluate factors that may mitigate the sentences given to defendants, such as cooperation with law enforcement, admission of guilt, and repentance. The aim is to balance justice with efforts to reform defendants' behavior.This research analyzes drug offenses based on the verdict of the Makassar District Court in case number 816/Pid.Sus/2023/PN. Mks. The study employs a normative juridical approach to assess the application of law in cases of drug abuse, focusing particularly on the court's decision.The findings reveal that the Makassar District Court's verdict in this case was deemed ineffective as the imposed punishment did not deter the perpetrator, despite clear evidence that the defendant, Risman Jalali Alias Chris, committed a criminal offense involving Class I narcotics for purposes other than personal use, as alleged. Therefore, the defendant received a sentence of 1 year and 6 months in prison, with the time spent in pretrial detention deductedThis evaluation highlights challenges in law enforcement, rehabilitation, and efforts to prevent drug abuse. Prevention and educational initiatives are crucial to reducing drug-related crimes. Therefore, comprehensive approaches are necessary, encompassing effective law enforcement, holistic rehabilitation programs, and sustained efforts in prevention and education.